Multi-Targeting Andrographolide, a Novel NF-κB Inhibitor, as a Potential Therapeutic Agent for Stroke - Yang, Chih-Hao (Int J Mol Sci, 2017)
A key focus in the field of drug discovery has been motivated by the neuroprotection of natural compounds. Cerebral ischemia is a multifaceted pathological process with a series of mechanisms, and a perspective for the development of neuroprotectants from traditional herbal medicine or natural products is a promising treatment for this disease. Natural compounds with the effects of anti-oxidation, anti-inflammation, anti-apoptosis, and neurofunctional regulation exhibit therapeutic effects on experimental ischemic brain injury. Conferring to the pharmacological mechanisms underlying neuroprotection, a study found that androgapholide, a diterpene lactone compound, exhibits varying degrees of neuroprotective activities in both in vitro and in vivo experimental models of stroke. The neuroprotective mechanisms of andrographolide are suggested as: (I) increasing nuclear factor E2-related factor 2-heme oxygenase (Nrf2-HO-1) expression through p38-mitogen activated protein kinase (MAPK) regulation, (II) inducing cerebral endothelial cells (CEC) apoptosis and caspase-3 activation, (III) down regulating Bax, inducible nitric oxide synthase (iNOS), and (IV) inhibiting hydroxyl radical (OH(−)) formation, and activating transcription factor NF-κB signaling pathways. Recently, several researchers have also been trying to unveil the principal mechanisms involved in the neuroprotective effects of andrographolide. Therefore, this review aims to summarize an overview on the neuroprotective effects of andrographolide and exemplifies the essential mechanisms involved. This paper can provide information that andrographolide drug discovery may be a promising strategy for the development of a novel class of neuroprotective drug.